Alarming Prevalence of Nosocomial Pseudomonas aeruginosa among Patients with Infected Burn Wounds - Jubair, Kadhum H.; Alkhudhairy, Miaad K. (Medical Science Journal for Advance Research, 2024)
Background: Recently, the prevalence of nosocomial Pseudomonas aeruginosa has become a concern due to its involvement in increased morbidity and mortality, especially those highly virulent strains associated with burn wounds in burn centers. Therefore, this cross-sectional study aimed to isolate and determine the prevalence of nosocomial Pseudomonas aeruginosa among burned inpatients. This study was carried out between September 2023 and March 2024. A total of 355 pus, purulent fluid and necrotic tissue swabs were obtained from burn victims with burns at the Burn Centers in Najaf City, Iraq. 85/355 (23.9%) of isolates under study were detected as Pseudomonas aeruginosa based on laboratory methods (microscopic, biochemical and culture). All test isolates appeared to grow optimally on cetrimide and chromium agar media, and colonies appeared green on these media when examined by the naked eye and greenish fluorescence under ultraviolet light. However, colonies on blood agar were bright and metallic, and the most common type of lysis was β-hemolysin followed by α-hemolysin. On Nutrient agar, most of the isolates were characterized by positive multi-pigment production 57/85 (67.1%), while 28/85 (32.9%) of the isolates were negative pigment production. Conclusion: The rate of virulent P. aeruginosa in the current study raises the degree of alarm, especially among burn patients because they do not have the means of defense that qualify them to resist this virulent pathogen. Also, the older age groups were more affected by it, which increases the levels of risk because elderly patients have weak immunity in addition to most of them being infected with other diseases such as diabetes, which increases the complications associated with burn infections. The impact of Pseudomonal infections on females in most age groups was one of the results of utmost importance and the real reasons behind it must be known. According to numerous studies and reports, the possession of this dangerous pathogen of multiple virulence factors such as its ability to form biofilms delays or prevents the patient's recovery and increases the likelihood of death in burn inpatients. Also, the possession of these virulent bacteria of a large genome makes them exceptionally adaptable and resistant to unfavorable environments.